Impact of extreme rainfall shocks on the educational performance of vulnerable urban students: evidence from Brazil - Francisca Letícia Ferreira de Lima; Rafael Barros Barbosa; Alesandra de Araújo Benevides; Fernando Daniel de Oliveira Mayorga (EconomiA, 2024)
Purpose: This paper examines the impact of extreme rainfall shocks on the performance in test scores of students living near at-risk urban areas in Brazil. Design/methodology/approach: To identify the causal effect, we consider the exogenous variation of rainfall at the municipal level conditioned on the distance from the school to risk areas and the rainfall intensity in the school months. Findings: The results suggest that extreme precipitation shocks, defined as a shock of at least three months of high-intensity rainfall, have an adverse impact on both math and language performance. Through a heterogeneous effects analysis, we find that the impact varies by student gender, with girls being more affected. In addition, among students who study near at-risk areas, those with better previous school performance and higher socioeconomic status are more negatively affected. Originality/value: Our results suggest that extreme weather events can increase the differences in human capital accumulation between the population living near risk areas and those living more distant from these areas.
Keywords: 330; Educational performance; Extreme rainfall shocks; Risk areas